Development of Power Point Macro-Based Interactive Multimedia in Learning Islamic Cultural History in Improving Student Learning Outcomes - Hilda Amalia Khasanah; Kustiono Kustiono; Samsudi Samsudi (Innovative Journal of Curriculum and Educational Technology, 2023)
The history of Islamic culture (SKI) learning process so far has taught teachers using conventional methods with minimal use of information technology which has an impact on low interest and student learning outcomes that are not in accordance with Article 19 paragraph 1 of Government Regulation No. 19 of 2005.This study aims to describe the learning characteristics of Islamic Cultural History in schools, develop learning media in the form of interactive learning multimedia, analyze the feasibility of SKI interactive learning multimedia, analyze SKI interactive learning multimedia in improving student learning outcomes. This type of research uses research and development (Research and Development) using the ADDIE model. The primary data collection technique is from the validation of media experts and material experts as well as the results of the pretest and posttest. The results of this study indicate that 1) SKI teachers teach in a teacher-centered way with the majority guided by LKS and SKI package books as learning resources, there are limitations to the use of media and technology where the media that is often used are blackboards and writing tools. 2) The results of the review by media experts and material experts state that the interactive multimedia based on PowerPoint macro enable that has been developed meets the criteria of being tested. 3) Development of interactive multimedia based on PowerPoint macro enable obtains very feasible criteria with an average percentage of 85.85%. 4) Interactive multimedia based on PowerPoint macro enable has a significant effect on student learning outcomes with the results of the small-scale hypothesis test obtaining 0.001 â‰¤ Î± 0.05 and the results of the hypothesis on a large scale obtaining 0.000 â‰¤ Î± 0.05. The gain test results on a small scale gets 0.7806 with high criteria and on a large scale gets 0.6187 with medium criteria.